Molecular Detection of β-Giardin Gene of Giardia lamblia in Peptic Ulcer Patient in Babylon Province (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
background: Giardia lamblia is one of the  commonest human intestinal protozoa, it cosmopolitan  and is endemic throughout the world with a wide range of mammalian hosts.Objective: This object aimed to focus on molecular detection of β-Giarin gene of Giardia lamblia  in patient with peptic ulcer to investigate an association between Giardia lamblia and Helicobacter pylori infection.  Methods: a total of 64 stool sample were collected from patients  attending to endoscopy unit (specialized Marjan Hospital for Internal and Cardiac Diseases   in Babyoln province) for their peptic ulcer symptoms And were positive for H. pylori.  Polymerase chain reaction was achived by primers that targeted the (β-Giardin) gene (218pb) of Giardia lamblia.Results: in this study 64 stool sample were collected from patients with peptic ulcer,  Giardia lamblia infection was found in 12 (18.7%)  according to direct examination of stool sample, while 21 (32.8%) was positive to giardiasis when used PCR for detection of β-Giardin gene (218pb) ,also the percentage of infection in  male was significantly (p